A cross-sectional study on awareness and practice of universal precautions among laboratory technicians of a tertiary health care facility - Roohen, Sara; Bhavani, Kenche; Vemuri, Jyothi Lakshmi Naga; Anjum, Shabnam (International Journal Of Community Medicine And Public Health, 2020)
Background: Biological hazards and health safety issues are a special concern in laboratory technicians who handle blood, body fluids, and tissues which may contain infectious agents. Lack of knowledge of standard precautions has been noted to influence the practice and behaviour change in relation to these precautions requires knowledge. This study therefore aims to study the awareness and practice of universal precautions (U.P) in lab technicians. Methods: Cross sectional type of study was conducted in the tertiary health care facility (Osmania General Hospital) in Hyderabad district among laboratory technicians of various departments from 1-20/11/18. Random sampling was done and data was collected using a self-administered questionnaire. Statistical analyses were performed using Microsoft excel 07. Descriptive analysis was done and Chi-square tests were used for establishing association. Results: The mean age of the respondents was 32.37 years, all of them were graduates by education and the mean length of experience was 5.45 yrs. The mean score for knowledge was 14 (41.1%). In the domain of practice, the responses were quite satisfactory with majority of the responses being “always” for all the practices, wearing eye shields and face masks was only “sometimes” followed and majority of “not applicable” were for wearing gloves Conclusions: Although standard and isolation precautions are introduced, the overall performance of respondents was unsatisfactory.